Prevalence and changes of low-value care at acute care hospitals: a multicentre observational study in Japan - Yasuharu Tokuda; Yasuki Kobayashi; Atsushi Miyawaki; Yusuke Tsugawa; Kazuaki Sano; Rei Goto; Ryo Ikesu (BMJ Open, 2022)
Objectives We aimed to examine the use and factors associated with the provision of low-value care in Japan.Design A multicentre observational study.Setting Routinely collected claims data that include all inpatient and outpatient visits in 242 large acute care hospitals (accounting for approximately 11% of all acute hospitalisations in Japan).Participants 345 564 patients (median age (IQR): 62 (40–75) years; 182 938 (52.9%) women) seeking care at least once in the hospitals in the fiscal year 2019.Primary and secondary outcome measures We identified 33 low-value services, as defined by clinical evidence, and developed two versions of claims-based measures of low-value services with different sensitivity and specificity (broader and narrower definitions). We examined the number of low-value services, the proportion of patients receiving these services and the proportion of total healthcare spending incurred by these services in 2019. We also evaluated the 2015–2019 trends in the number of low-value services.Results Services identified by broader low-value care definition occurred in 7.5% of patients and accounted for 0.5% of overall annual healthcare spending. Services identified by narrower low-value care definition occurred in 4.9% of patients and constituted 0.2% of overall annual healthcare spending. Overall, there was no clear trend in the prevalence of low-value services between 2015 and 2019. When focusing on each of the 17 services accounting for more than 99% of all low-value services identified (narrower definition), 6 showed decreasing trends from 2015 to 2019, while 4 showed increasing trends. Hospital size and patients’ age, sex and comorbidities were associated with the probability of receiving low-value service.Conclusions A substantial number of patients received low-value care in Japan. Several low-value services with high frequency, especially with increasing trends, require further investigation and policy interventions for better resource allocation.